Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island - Kruskop, Sergei V.; Kawai, Kuniko; Tiunov, Mikhail P. (Zootaxa, 2019)
Until recently, almost all barbastelle populations inhabiting Asia, from Iran to Japan and Taiwan, were recognized as a single species, Barbastella darjelingensis. However, in recent years, it was shown that the taxonomic diversity within the genus Barbastella was underestimated, and B. darjelingensis sensu lato is highly variable, both morphologically and genetically. Transcaucasian and Central Asian populations were already raised to the species level as B. caspica. Populations from eastern and south-eastern Asia are still understudied and likely encompass undescribed species. Comparing results from mtDNA sequences, skull morphometry and baculum shape, we concluded that one of these putative species is represented by populations inhabiting Honshu, Hokkaido and Kunashir Islands, and provide a scientific description of this new species. Populations from Taiwan, southern China and Indochina represent a sister mitochondrial clade to this new species. However, available morphological material from these areas did not demonstrate a significant difference from the Himalayan B. darjelingensis. Therefore, we refuse to give this form any taxonomic status until further studies of more vast material are done.